1979
DOI: 10.3109/inf.1979.11.issue-1.06
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Cepacia in 16 Non-Fatal Cases of Postoperative Bacteremia Derived from Intrinsic Contamination of the Anaesthetic Fentanyl: Clinical and Epidemiological Observations in Denmark and Holland

Abstract: From Nov. 15 to Dec. 17, 1977, Pseudomonas cepacia was isolated from the blood of 16 patients in Odense, Denmark, and Nijmegen, Holland, 2--5 days after an operation with general anaesthesia. The fever started 14--70 h after operation and lasted 2--4 days. All patients recovered. 14/15 patients examined 7--51 days later had agglutinating antibody titres of 400-3,200 against the epidemic strain. Ps. cepacia with identical biochemical characters and sensitivity pattern was isolated from unbroken vials containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Its natural habitat is soil, water and vegetation, but acquisition of this pathogen is often associated with hospitals; nosocomial postoperative infections of the urinary tract (Mitchell and Hayward 1966) and wounds (Bassett et al . 1970) have been traced to water‐borne contamination of disinfectant solutions, in Sweden postoperative bacteraemia in 16 patients was attributed to the contaminated anaesthetic fentanyl (Siboni et al . 1979), and two severely burned patients developed nosocomial septicaemia during treatment (Brauner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Its natural habitat is soil, water and vegetation, but acquisition of this pathogen is often associated with hospitals; nosocomial postoperative infections of the urinary tract (Mitchell and Hayward 1966) and wounds (Bassett et al . 1970) have been traced to water‐borne contamination of disinfectant solutions, in Sweden postoperative bacteraemia in 16 patients was attributed to the contaminated anaesthetic fentanyl (Siboni et al . 1979), and two severely burned patients developed nosocomial septicaemia during treatment (Brauner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial epidemics of P. cepacia bloodstream infections have been the subject of at least 15 separate reports involving a variety of different reservoirs and different modes of transmission (1,7,8,10,11,18,25,28,31,34,36,40,45,47,CDC unpublished data).…”
Section: Bloodstream Infectionsmentioning
confidence: 99%
“…In 3 investigations, the source of P. cepacia infections was intrinsic contamination of commercial intravenous products (36,40,47) (Table 1 ). Siboni et al (36) reported that outbreaks of bloodstream infections in Holland and Denmark were due to intrinsic contamination of the intravenous anesthetic Fentanyl*.…”
Section: Bloodstream Infectionsmentioning
confidence: 99%
See 2 more Smart Citations